PROBLEMS OF ENVIRONMENTAL HEALTH: RETROSPECTIVE ANALYSIS ON THE EXAMPLE IRKUTSK OBLAST - N. V. Efimova (Acta Biomedica Scientifica)
The article presents important medico-ecological problems: preservation of an effect of influence of air pollution in the subsequent generations; environmental and medical consequences of the cumulative ecological danger; taking into account regional features at the harmonization of hygienic standards; use of modern approaches to formation of target preventive programs. Relevance of these problems is observed on the example of Irkutsk region. Irkutsk region is one of the largest advanced industrial subjects of Russian Federation. The leading industries are energy, pulp-and-paper and chemical, wood and woodworking, nonferrous metallurgy, mechanical engineering. Concentration of the industry in the south of the region has led to high man-caused environmental load. Under conditions of reduced ability to self-purification of environmental objects this fact results in formation of zones of ecological trouble. Environmental and medicosocial problems occurring in a long-term technogenic mercury pollution are very important and require more systematic studies. Bratsk water reservoir is strongly polluted by technogenic Hg. Among rural population living near the toxicant sources the signs of unfavorable mercury effects have been revealed: mercury microcirculation in the organism (10,5 % of cases with group level urinary mercury > 5,2 microg/l), disorders of vegetative nervous system (87 % in intact group vs 43 % in the group of comparison; р ≤ 0,05) and pathology of thyroid glands (14,6 % children in intact group vs 8,1 % in the group of comparison; р ≤ 0,05). The aims of ecological medicine must include prevention as well as safe remediation and translational therapeutic intervention in human populations after exposures. The conception of development of the programs aimed at the coordination of activity of preventing ecologically caused losses was proposed.